Managing several simultaneous lines of talk in Finnish multi-party mobile messaging. (March 2021) - Virtanen, Mikko T.; Vepsäläinen, Heidi; Koivisto, Aino
Highlights: Simultaneous lines of talk are an integral part of mobile group messaging. Parallel activities are managed by both adapted and emergent practices. Practices related to platform-afforded reply-marking are unstable. Notions based on the idea of monoactivity need reevaluating in study of online talk. Abstract: As smartphones have become an integral part of the everyday life of many, we have seen a proliferation of private messaging groups in mobile apps such as WhatsApp. One characteristic of group messaging is the constant presence of multiple simultaneous lines of talk – even more so than in the dyadic mode. In this article, we explore the linguistic and technologically afforded practices of managing simultaneous lines of talk – topics, sequences, larger activities - in mobile group messaging. Specifically, we analyze (i) how new lines of talk are initiated next to already existing ones, (ii) how two prior messages are responded to consecutively, and (iii) how non-adjacent messages are responded to. Our data consist of Finnish instant group messaging, and the analysis was conducted using the Conversation Analytic method. Our study complements previous studies on the management of multiple lines of talk in mobile messaging, and more generally, multiactivity in social interaction. In particular, it presents new insights into how practices such as 'and'-prefacing, action-labelling and platform-provided reply-marking are utilized for organizing parallel activities.